Case Study : NZ Kedai Kek & Roti / Nur Syuhada Shobir - Shobir, Nur Syuhada (2020)
The chosen SMEs is NZ Bakery that offer their services on sells the buns and cakes. Other than that, they also received order for the event in large quantity such as for schools, hostels, company, birthday celebration and wedding ceremony. The interview session with both owner Encik Ahmad Tarmizi and Puan Jam binti Salleh about the company and their business giving me the information about their products, technology used, the marketing technique and etc that briefly explained in this report. The information got during interview can be used to analyse the SWOT analysis technique on the strength, weakness, opportunity and threats towards the company. The findings about the issues faced by the company related to the technology are stated in this report.